Influence of strontium and magnesium on serum calcium concentrations (Revista Española de Fisiología, 1991)
Twenty four male Wistar rats weighing 250 +/- 10 g, in three groups of 8 rats each, were used. Group A was used as control and the content of its drinking water was 6.5 mg/l Ca; 2.4 mg/l Mg. The drinking water of groups B and C was supplemented with 20 mM (SrCl2) and 20 mM (MgCl2), respectively. Once the 20 days of mineral supplementation had passed, arterial blood was extracted by puncture in the abdominal aorta. In the serum obtained after centrifugation, Ca, Mg, Sr and the total proteins (TP) were determined. Afterwards the serum was subjected to ultrafiltration. Concentrations of Ca, Mg and TP were measured in the obtained ultrafiltrates (u), with the above described techniques. The pH was measured before and after the ultrafiltration. The TP decreased significantly both in group B (supplemented with Sr), and in group C (supplement with Mg). Increases in Ca were found in group B and in Mg in group C. The Mg/Ca ratio increased 10% after the supplementation with Mg. At the ultrafiltrate a significant increase in Cau after supplementation with Sr and with Mg was observed. The Mgu/Cau ratio decreased 14% in the group supplemented with Sr and 38% after the supplementation with Mg. In conclusion, the supplementation with Sr (20 mM) in rats increases the Cau and could have the effect of reducing protein synthesis. These facts should be borne in mind when Sr is used for therapeutical purposes.